A cluster randomized controlled trial of a client-centred, activities of daily living intervention for people with stroke: one year follow-up of caregivers. (August 2016) - Bertilsson, Ann-Sofie; Eriksson, Gunilla; Ekstam, Lisa; Tham, Kerstin; Andersson, Magnus; von Koch, Lena; Johansson, Ulla
Objective: Compare caregiver burden, provision of informal care, participation in everyday occupations and life satisfaction of caregivers to people with stroke, who either had received a client-centred, activities of daily living intervention or usual activities of daily living interventions. Design: A multicentre cluster randomized controlled trial in which 16 rehabilitation units were randomly assigned to deliver a client-centred, activities of daily living intervention or usual activities of daily living interventions. Caregiver outcomes were compared cross-sectionally at 12 months and changes in outcomes between three and 12 months after people with stroke were included in the study. Setting: Inpatient and outpatient rehabilitation. Participants: Caregivers of people with stroke enrolled in the trial. Intervention: A client-centred, activities of daily living intervention aiming to increase agency in daily activities and participation in everyday life for people after stroke. Main measures: Caregiver Burden Scale, Occupational Gaps Questionnaire, LiSat-11. Results: There were no differences in outcomes between caregivers in the client-centred, activities of daily living ( n  = 88) and the usual activities of daily living ( n  = 95) group at 12 months. The caregiver burden score was 42.7 vs. 41.8, p  = 0.75, mean occupational gaps were 3.5 vs. 4.0, p  = 0.52 and satisfaction with life was 53% vs. 50%, p  = 0.87. There were no differences in changes between three and 12 months. However, within groups there were significant differences in caregiver burden, factor general strain, for caregivers in the client-centred, activities of daily living group, and in provision of informal care for the usual activities of daily living group. Conclusion: The client-centred intervention did not bring about any difference between caregiver-groups, but within groups some difference was found for caregiver burden and informal care.